2001
DOI: 10.1242/jcs.114.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Akt inhibits NGF-induced growth arrest and neuronal differentiation of PC12 cells

Abstract: To investigate the role of Akt in nerve growth factor (NGF)-induced neuronal differentiation, PC12 cells ectopically expressing wild-type or dominant-inhibitory forms of Akt were analyzed. NGF-induced neurite outgrowth was greatly accelerated in cells expressing dominant-inhibitory Akt, compared to parental PC12 cells, but was almost completely blocked in cells expressing wild-type Akt. Since neuronal differentiation requires an arrest of cell growth, several aspects of cell growth of the different cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…57,59,60 Furthermore, the overexpression of active forms of PKB in cells has also been shown to promote differentiation of some cells [61][62][63] while inhibiting the differentiation of others. 64,65 It is likely that these processes are mediated by PKB phosphorylating a number of key regulators of cellular function, and much of the work in this area is aimed at identification and characterization of these substrates.…”
Section: Pkb May Be a Key Mediator Of Cell Survival Cell-cycle Regula...mentioning
confidence: 99%
See 1 more Smart Citation
“…57,59,60 Furthermore, the overexpression of active forms of PKB in cells has also been shown to promote differentiation of some cells [61][62][63] while inhibiting the differentiation of others. 64,65 It is likely that these processes are mediated by PKB phosphorylating a number of key regulators of cellular function, and much of the work in this area is aimed at identification and characterization of these substrates.…”
Section: Pkb May Be a Key Mediator Of Cell Survival Cell-cycle Regula...mentioning
confidence: 99%
“…These results demonstrated that overexpression of activated PKB strongly inhibited apoptosis induced by many cellular insults that induce cell death (reviewed in refs and ). Overexpression of active forms of PKB in insulin-responsive cells induced many processes that are normally activated by insulin such as glycogen synthesis and protein synthesis, , stimulated uptake of nutrients such as glucose and amino acids, , and also induced certain changes in gene expression that are induced by insulin and growth factors. ,, Furthermore, the overexpression of active forms of PKB in cells has also been shown to promote differentiation of some cells while inhibiting the differentiation of others. , It is likely that these processes are mediated by PKB phosphorylating a number of key regulators of cellular function, and much of the work in this area is aimed at identification and characterization of these substrates.…”
Section: Pkb May Be a Key Mediator Of Cell Survival Cell-cycle Regula...mentioning
confidence: 99%
“…Akt has been related to have positive effects on neurite growth (Kumar et al., 2005; Okada et al., 2010), but some reports also suggest that this protein has a negative effect on neurite growth (Bang et al., 2001; Miyamoto et al., 2013). To explore the possibility that the effects of antioxidants on neurite growth could be mediated by an increase of p‐Akt (Ser473) levels, cultures were treated at 2 DIV with the PI3K inhibitor LY294002 for 30 min and then cells were incubated with Euk‐134 and 24 h after neurite growth was measured.…”
Section: Resultsmentioning
confidence: 99%
“…This means that it is not possible to use this line to assess epigenetic changes, e.g., after 2, 3, or 4 cycles of BTZ therapy, thus mimicking typical clinical conditions. However, according to the available literature [ 46 , 47 , 48 , 49 , 50 , 51 ], this problem would likely also occur in other non-proliferating neuronal lines with a standard cell culture time of 21 days. Simultaneously, for the same reasons, it is not possible to reliably assess the reversibility of the detected epigenetic changes after the conducted experiment.…”
Section: Discussionmentioning
confidence: 99%